Maternal Body Mass Index Moderates the Influence of Smoking Cessation on Breast Feeding - Vurbic, Drina (Oxford University Press, 2014)
INTRODUCTION: Smoking cessation is associated with greater breast feeding in newly postpartum women, while being overweight or obese is associated with lower rates of breast feeding. The purpose of this study is to examine whether the increases in breast feeding associated with smoking cessation are moderated by maternal body mass index (BMI). To our knowledge, the interaction of maternal smoking status and overweight/obesity on breast feeding has not been previously reported. METHODS: Participants (N = 370) were current or recent smokers at the start of prenatal care who participated in controlled trials on smoking cessation or relapse prevention during/after pregnancy. Study participants were followed from the start of prenatal care through 24 weeks postpartum. Smoking status was biochemically verified, and maternal reports of breast feeding were collected at 2-, 4-, 8-, 12-, and 24-week postpartum assessments. RESULTS: Women who reported postpartum smoking abstinence or had a normal/underweight prepregnancy BMI (<25) were more likely to be breast feeding at the time that smoking status was ascertained (odds ratio [OR] = 3.02, confidence interval [CI] = 2.09–4.36, and OR = 2.07, CI = 1.37–3.12, respectively). However, smoking status and BMI interacted such that (a) normal/underweight women showed a stronger association between smoking abstinence and breast feeding (OR = 4.58, CI = 2.73–7.66) than overweight/obese women (OR = 1.89, CI = 1.11–3.23), and (b) abstainers showed an association between normal/underweight BMI and breast feeding (OR = 3.53, CI = 1.96–6.37), but smokers did not (OR = 1.46, CI = 0.88–2.44). CONCLUSIONS: Overweight/obesity attenuates the positive relationship between smoking abstinence and greater breast feeding among newly postpartum women.